Baculovirus as delivery system for gene transfer during hypothermic organ preservation - Murguía-Meca, F; Plata-Muñoz, J; Hitchman, R; Danquah, J; Hughes, D; Friend, P; Fuggle, S; King, L (2011)
Concerns over the safety of conventional viral vectors have limited the translation of gene transfer from an exciting experimental procedure to a successful clinical therapy in transplantation. Baculoviruses are insect viruses, but have the ability to enter mammalian cells and deliver potential therapeutic molecules with no evidence of viral replication. This study provides evidence of the ability of recombinant baculovirus to enter mammalian kidneys and livers during cold preservation. Six kidneys and six liver lobules retrieved from large pigs were perfused with University of Wisconsin (UW) solution containing a baculovirus tagged with green fluorescent protein and preserved for 8 h. In addition, six kidneys were perfused with UW containing a baculovirus expressing red fluorescent protein and preserved for 24 h. Green fluorescent virus particles were detected within transduced kidneys and livers after 8 h standard cold storage and red fluorescent protein mRNA was detected in kidneys after 24 h of cold preservation. There were no significant differences in tissue architecture, cell morphology or ATP content between experimental organs and their controls. Ex vivo transduction of organs with recombinant baculovirus during conventional cold preservation was demonstrated with no evidence of additional injury or reduction in cell viability. © 2011 European Society for Organ Transplantation.